2018
DOI: 10.1073/pnas.1812756115
|View full text |Cite
|
Sign up to set email alerts
|

Effects of protein size, thermodynamic stability, and net charge on cotranslational folding on the ribosome

Abstract: During the last five decades, studies of protein folding in dilute buffer solutions have produced a rich picture of this complex process. In the cell, however, proteins can start to fold while still attached to the ribosome (cotranslational folding) and it is not yet clear how the ribosome affects the folding of protein domains of different sizes, thermodynamic stabilities, and net charges. Here, by using arrest peptides as force sensors and on-ribosome pulse proteolysis, we provide a comprehensive picture of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
95
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 68 publications
(111 citation statements)
references
References 74 publications
12
95
0
Order By: Relevance
“…Compared to RNH*, the fFL diminishes with decreasing DGint for these variants, showing that we can tune the release of RNH* by adjusting the stability of the intermediate. In agreement with previous studies, the amplitude of fFL for these three-state variants correlates with global stability (24,25). Since the stability of the intermediate is related to the height of the subsequent folding barrier, this kinetic barrier may play a role.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Compared to RNH*, the fFL diminishes with decreasing DGint for these variants, showing that we can tune the release of RNH* by adjusting the stability of the intermediate. In agreement with previous studies, the amplitude of fFL for these three-state variants correlates with global stability (24,25). Since the stability of the intermediate is related to the height of the subsequent folding barrier, this kinetic barrier may play a role.…”
Section: Discussionsupporting
confidence: 92%
“…The connection between the biophysical properties of the nascent chain and the fFL remains unclear. The stability of the nascent chain, its topology, and folding rate have all been linked to the amplitude of the fFL (24,25). Thus, a comparison of FPA on the well-characterized protein RNH* with the on-ribosome energetics and kinetics obtained by pulse proteolysis should help to decipher these effects, in addition to reporting on the RNH* folding trajectory on the ribosome.…”
Section: Rnh* I53d Does Not Read Through the Secm Stall -mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, a number of new experimental methods for analyzing the cotranslational folding of protein domains have been developed. These include real-time FRET analysis [1], and methods in which nascent polypeptide chains of defined lengths are arrested in the ribosome and their folding status analyzed by, e.g., cryo-EM [2,3], protease resistance [1,[4][5][6][7][8][9], NMR [10][11][12][13][14][15], photoinduced electron transfer (PET) [1,16], folding-associated cotranslational sequencing [17], optical tweezer pulling [18][19][20][21], fluorescence measurements [22], and measuring the force that the folding protein exerts on the nascent chain using a translational arrest peptide (AP) as a force sensor [2,3,9,21,[23][24][25]. Further, coarse-grained molecular dynamics simulations of various flavors can provide detailed insights into cotranslational folding reactions [26][27][28][29][30], especially when coupled with experimental studies [3,26,31].…”
mentioning
confidence: 99%
“…The discovery 2,3 and engineering 4,5 of translational arrest peptides (APs) has provided us with a new tool to examine how proteins fold cotranslationally. To date, the folding of several small proteins and protein domains has been studied using the force-sensitive AP from the E. coli SecM protein with a method we have called Force-Profile Analysis (FPA) [6][7][8][9][10][11][12][13][14][15] . Recently, we demonstrated that FPA faithfully picks up cotranslational protein folding events observed by direct biophysical measurements 15 .…”
Section: Introductionmentioning
confidence: 99%